Implementation of Metallurgical Industry Management Using the DMAIC Method in TS Aluminum - Hafiz Faturrahman, Muhammad; Khayyan Bahiy, Oktavian; Carlotta, Nixon Carlotta; Amalia, Yasmina (Journal of Metallurgical Engineering and Processing Technology, 2024)
The case study in this research comes from the TS Aluminum company in Yogyakarta. This research aims to reduce the number of defects in metal in the casting process from an industrial management point of view. This research method uses quantitative and qualitative methods through literature studies and experimental data with the DMAIC method.From the results of production and marketing carried out with a production volume of 250 pcs per day, there were 4% failures in the products produced. Defects that often occur are rat tail defects, cold shot, and porosity. Defects are caused by factors such as human error, methodology, and materials. Recommendations for improvement include providing regular training to employees, updating work procedures, and checking materials.